OPTIMALISASI MATERIAL DAN PROFILE REINFORCEMENT BEAM GUNA MENINGKATKAN ENERGI SERAP BENTURAN BERBASIS SIMULASI FEM - Sukoco, Leonardo Paksi; Tohom, Frans; Pranoto, Ethys (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Bumpers are critical structures in passenger vehicles, designed to absorb low-speed impact energy. This study examines the effect of profile combinations (C-Hat and Double-Hat Section) and materials (Steel Bare/E.G.-H.F.80Y 100T, CFRP T700S, Aluminium 2024-T86) on MPV bumper reinforcement beam performance under UN ECE R.42 standards. Finite Element Method (FEM) simulations using ANSYS Explicit Dynamic with longitudinal impact tests (4 km/h) and side tests (2.5 km/h) were conducted to evaluate deformation, stress, and energy absorption. Results revealed that C-Hat Section with Aluminium 2024-T86 delivered optimal performance: von Mises stress 194.40 MPa, deformation 1.2057 mm, and energy absorption 160.31 J at 4 mm thickness. The Weighted Sum Model (WSM) analysis confirmed this combination as the best choice (score 1.773). The proposed design meets safety criteria while maintaining weight efficiency for MPV applications.